Gentle Sterilization of Carrot-Based Purees by High-Pressure Thermal Sterilization and Ohmic Heating and Influence on Food Processing Contaminants and Quality Attributes - Gratz, Maximilian; Sevenich, Robert; Hoppe, Thomas; Schottroff, Felix; Vlaskovic, Nevena; Belkova, Beverly; Chytilova, Lucie; Filatova, Maria; Stupak, Michal; Hajslova, Jana; Rauh, Cornelia; Jaeger, Henry (Frontiers in Nutrition, 2021)
Pressure-enhanced sterilization (PES) and ohmic heating (OH) are two emerging sterilization techniques, currently lacking implementation in the food industry. However, both technologies offer significant benefits in terms of spore inactivation using reduced thermal intensity in food products, as well as minimized effects on sensory and nutritional profiles. In this study, PES and OH were tested based on possible food safety process windows in comparison to thermal retorting, to optimize the food quality of carrot-based purees. The following parameters related to food quality were tested: texture, carotenoid content, color, and detectable amount of food processing contaminants (FPC) formed. Application of the innovative sterilization techniques resulted in a better retention of color, texture, and carotenoids (for PES) as well as a reduced formation of food processing contaminants. Importantly, a significant reduction in the formation of furan and its derivates was observed, compared to the retorted samples. Hence, both sterilization technologies showed promising results in the mitigation of potential toxic processing contaminants and retention of quality attributes.